Nutritional Management of Moderate- and Late-Preterm Infants Commenced on Intravenous Fluids Pending Mother's Own Milk: Cohort Analysis From the DIAMOND Trial - Alexander, Tanith; Meyer, Michael; Harding, Jane E.; Alsweiler, Jane M.; Jiang, Yannan; Wall, Clare; Muelbert, Mariana; Bloomfield, Frank H., The DIAMOND Study Group (Frontiers in Pediatrics, 2022)
Background: Exclusive breastmilk is the desired enteral nutrition for babies born moderate- and late-preterm between 32+0-36+6 weeks' gestation; however, this goal is often difficult to achieve. Methods: Prospective cohort of babies 32+0-35+6 weeks' gestation enrolled in the DIAMOND trial, who were randomised to a condition specifying babies should receive mother’s own milk (MOM) as the only enteral feed. Factors associated with successful transition to MOM, defined as MOM being the sole enteral feeding at the time of first cessation of intravenous (IV) fluids, were investigated by logistic regression. Time to commencement of a milk other than MOM was analysed by Kaplan-Meier survival curves. Results: 151 eligible babies (60% boys) were included, 93 (63%) of whom successfully transitioned from IV fluids onto MOM only. Alternative milks, mostly formula, were used to transition from IV fluids onto enteral feeds more often in multiples and Māori, and was commenced earlier in Māori than other ethnicities (p=0.007) and in late-preterm compared with moderate-preterm babies (p=0.01). Receiving exclusively breastmilk at discharge was more likely for babies who successfully transitioned from IV fluids onto MOM only (OR (95% confidence intervals) 4.9 (2.3 – 10.6)) and who received only MOM in the first week after birth (4.8 (2.2 – 10.4)), both p <0.0001. Receiving exclusively breastmilk at discharge was less likely for Māori than Caucasian babies (0.2 (0.1 – 0.6), p<0.0006). There was no difference in use of alternative milks between babies who received parenteral nutrition or dextrose, nor between small-for-gestational-age and appropriate-for-gestational-age babies. Conclusions: Despite an intention to provide only MOM, significant numbers of moderate- and late-preterm babies received formula to transition from IV fluids, and this differed by ethnicity. The drivers underlying these decisions require further investigation. These data highlight an urgent need for quality initiatives to support and encourage mothers of moderate- and late-preterm babies in their lactation.